Incidental ureteral fibroepithelial polyp - Köseoğlu, Hikmet (Proc (Bayl Univ Med Cent), 2020)
Although rare, fibroepithelial polyp of the ureter is the most common type of benign urinary tract mesodermal tumor. It may cause symptoms such as hematuria, dysuria, and flank pain or be asymptomatic. Here we report incidental intraoperative detection of a left ureteral fibroepithelial polyp during an elective gyno-oncological surgery for left-sided ovarian thecoma.